Knowledge and attitudes regarding medical research studies among patients with breast cancer and gynecological diseases - Lux, Michael P.; Hildebrandt, Thomas; Knetzger, Sandra-Maria; Schrauder, Michael G.; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Fasching, Peter; Beckmann, Matthias; Thiel, Falk (BMC Cancer, 2015)
Medical research studies are becoming increasingly important for optimizing the prevention, diagnosis and treatment of illnesses. Participation in research studies can have many benefits for patients. In randomized and controlled clinical studies, they can receive the best possible medical care currently available. However, only a small proportion of patients nowadays are treated within the framework of medical research. The primary endpoint of this study was to discover what level of knowledge patients have about clinical studies and how they currently perceive them, in order to identify ways of optimizing the information provided about studies from the patients' point of view.The study included 2546 patients (breast cancer 21.6%, gynecological cancer 8.3%, obstetrics 32.7%, endometriosis 7.8%, fertility treatment 3.2%, other benign gynecological illnesses 19.2%, no information for 7.2%) in the outpatient clinic (45.2%) and in the in-patient sector (54.8%) at the Department of Gynecology at Erlangen University Hospital and associated centers. In the single-center study, conducted between January 2011 and January 2012, the patients were asked about their level of knowledge regarding the background to medical research studies and the ways in which they are carried out and used. The patients were also asked how they perceived medical studies and how they thought study conditions might be optimized. The three-page questionnaire was included in the feedback sheet received by patients as part of the hospital's quality management system.As a whole, the group only had moderate knowledge about clinical studies. A majority of the respondents considered that studies were valuable (91.6%), but only a few were also willing to take part in them (58.4%). Knowledge and willingness to participate strongly depended on age (P < 0.001), educational level (P < 0.001) and patient group (P < 0.001). Most patients would prefer to decide about participating in studies through a discussion with their outpatient physicians.The information that patients have about clinical studies affects whether they participate in them. It is therefore extremely important for patients to be well informed, for their anxieties about participation to be relieved, and for the benefits of participation to be explained to them.
EVALuna2:17441